2020
DOI: 10.1002/smll.201907674
|View full text |Cite
|
Sign up to set email alerts
|

Mass Cytometry and Single‐Cell RNA‐seq Profiling of the Heterogeneity in Human Peripheral Blood Mononuclear Cells Interacting with Silver Nanoparticles

Abstract: Understanding the interactions between nanoparticles (NPs) and human immune cells is necessary for justifying their utilization in consumer products and biomedical applications. However, conventional assays may be insufficient in describing the complexity and heterogeneity of cell–NP interactions. Herein, mass cytometry and single‐cell RNA‐sequencing (scRNA‐seq) are complementarily used to investigate the heterogeneous interactions between silver nanoparticles (AgNPs) and primary immune cells. Mass cytometry r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 87 publications
2
29
1
Order By: Relevance
“…Significant cellular associations of Ag NPs were observed in monocytes and dendritic cells (DC), which is in good agreement with the previous studies [32,33] and current understanding of the cellular association of NPs; since monocytes are prominent antigen-presenting cells (APCs), they have a natural tendency to ingest foreign particles via phagocytosis [57,58]. Previous studies [34,55] have suggested that antigen-presenting cells recognize nanoparticles as foreign antigens, engulf and process them, then present them to effector cells via the major histocompatibility complex, thereby priming the antigen-specific cellular immune response.…”
Section: Discussionsupporting
confidence: 92%
“…Significant cellular associations of Ag NPs were observed in monocytes and dendritic cells (DC), which is in good agreement with the previous studies [32,33] and current understanding of the cellular association of NPs; since monocytes are prominent antigen-presenting cells (APCs), they have a natural tendency to ingest foreign particles via phagocytosis [57,58]. Previous studies [34,55] have suggested that antigen-presenting cells recognize nanoparticles as foreign antigens, engulf and process them, then present them to effector cells via the major histocompatibility complex, thereby priming the antigen-specific cellular immune response.…”
Section: Discussionsupporting
confidence: 92%
“…CyTOF was also instrumental in identifying a pro-inflammatory subset of macrophages that is involved in the development of HSCs ( 152 ). In addition, integrating CyTOF with scRNA-seq could provide additional discriminatory power for further sub-setting or functional analysis between distinct subsets of cells like HSCs and progenitors ( 153 ). Besides the precise immunophenotyping of cells in suspension, recent advances have enabled CyTOF of tissue sections or cells cultured on a slide.…”
Section: Technological Advances Towards the Molecular And Cellular Dissection Of The Hsc Microenvironmentmentioning
confidence: 99%
“…Moreover, a further development of the technology is represented by RNAseq at the single cell level, which is the most recent major achievement in transcriptomics analysis. Single cell analysis promises to finally dissect the subset subdivisions within the immune cell subpopulations [28]. Blood monocyte scRNAseq indicated that classical and non-classical monocytes belong to two major transcriptionally defined clusters [29].…”
Section: Monocytes: Different Subtypes For Different Functional Rolesmentioning
confidence: 99%